2018
DOI: 10.1097/icu.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in wavefront-guided LASIK

Abstract: Improvements in wavefront aberrometry, and also femtosecond and excimer lasers, have continued to improve our ability to correct refractive errors. Wavefront-guided LASIK remains a well tolerated and effective keratorefractive procedure, with a trend toward superiority. Nonetheless, further studies comparing this modality to others are needed to define the role each can serve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…The goal of subspecialty training fits well with the desire of fellowship-seeking residents to acquire special skills and to work with new technology. Recent advances in technology, such as refractive surgery technology and microinvasive glaucoma surgical techniques, have revolutionized multiple ophthalmic subspecialties, [11][12][13] which motivates residents to seek fellowship training to obtain skills to work with new technology. The constant popularity of cornea, glaucoma, and retina fellowships parallels the higher numbers of fellowship positions available in these fields.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of subspecialty training fits well with the desire of fellowship-seeking residents to acquire special skills and to work with new technology. Recent advances in technology, such as refractive surgery technology and microinvasive glaucoma surgical techniques, have revolutionized multiple ophthalmic subspecialties, [11][12][13] which motivates residents to seek fellowship training to obtain skills to work with new technology. The constant popularity of cornea, glaucoma, and retina fellowships parallels the higher numbers of fellowship positions available in these fields.…”
Section: Discussionmentioning
confidence: 99%
“…PRK is accepted as an effective and desirable method of treating refractive errors, but regression of refractive error and haze are challanges for PRK treatment especially in high diopters [1,9]. Wavefront-guided LASIK is a welltolerated and effective keratorefractive procedure with a trend superiority [10]. Miraftab [11] et al reported that UDVA improvement was superior in FS-LASIK when compared with PRK, but the two methods did not significantly differ in terms of CDVA improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A higher-order aberrometer can be used in refractive surgery to improve postoperative visual quality [15,16]. iDesign (Johnson & Johnson Vision, Santa Ana, CA, USA) is a new-generation aberrometer designed based on Hartmann-Shack theory to eliminate HOAs after refractive surgery and improve final visual quality.…”
Section: Introductionmentioning
confidence: 99%
“…iDesign (Johnson & Johnson Vision, Santa Ana, CA, USA) is a new-generation aberrometer designed based on Hartmann-Shack theory to eliminate HOAs after refractive surgery and improve final visual quality. Surgery using iDesign is referred to as wavefront-guided refractive surgery and has provided satisfactory results in many patients, so HOAs measured by iDesign may be crucial in determining visual quality [15][16][17][18][19][20][21]. Moreover, iDesign improves accuracy and resolution of HOAs measurements since it has more detection points and greater resolution than other aberrometers [16].…”
Section: Introductionmentioning
confidence: 99%